Strategi Konfrontatif Rusia Melalui Kebijakan Operasi Militer Khusus ke Ukraina - Hafid Adim Pradana; Ubaidah Adielah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This study aims to explain the background of the special military operation carried out by Russia against Ukraine. The special military operation launched by Russia against Ukraine made Russia accept various economic and political pressures from Western countries. The many negative impacts that Russia has had after the policy of a special military operation against Ukraine at first glance shows that Russia's actions are something that seems irrational. By using the theory of strategy in policy making formulated by John P. Lovell and the causal explanation method, this research results in the finding that the special military operations policy set by Vladimir Putin is a manifestation of the implementation of a confrontational Russian strategy based on two things, namely: the perception of threats to Ukraine's intention to join NATO and the superiority of Russia's capabilities over Ukraine.